2010
DOI: 10.4111/kju.2010.51.9.596
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Partial and Radical Nephrectomy for pT1b Renal Cell Carcinoma

Abstract: PurposePartial nephrectomy (PN) for patients with T1a renal cell carcinoma (RCC) has increasingly become accepted, although its role for patients with T1b RCC remains controversial. We retrospectively evaluated and then compared the oncologic and functional outcomes of patients with pT1b RCC who were treated with PN or radical nephrectomy (RN).Materials and MethodsA total of 70 patients who were diagnosed with pT1bN0M0 RCC between January 1995 and December 2004 were included. The 5-year overall survival (OS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…The main advantage of PN includes maximal preservation of renal parenchyma, which helps to avoid end-stage renal disease [19], [20]. There was no clear evidence that PN was associated with an inferior oncological outcome with stage T1a-T1b or even T2 cancer [4], [5].…”
Section: Discussionmentioning
confidence: 99%
“…The main advantage of PN includes maximal preservation of renal parenchyma, which helps to avoid end-stage renal disease [19], [20]. There was no clear evidence that PN was associated with an inferior oncological outcome with stage T1a-T1b or even T2 cancer [4], [5].…”
Section: Discussionmentioning
confidence: 99%
“…Several antecedent studies have indicated PN might be safely expanded to include patients with T1bN0M0 tumours [5,21–23]. In fact, as it pertains to these patients, Leibovich et al .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several antecedent investigations have indicated partial nephrectomy can safely be expanded to include patients with T1bN0M0 tumors. (Becker et al, 2006a;Kim et al, 2010;Mitchell et al, 2006;Patard et al, 2004) Leibovich and colleagues reported cancer-specific survival rates at 5 years of 98% for those receiving nephron-sparing surgery and 86% for patients treated with radical nehrectomy; and, after adjusting for several covariates including tumor grade and histologic subtype, this difference was found to no longer be statistically significant (risk ratio 1.60, 95% CI 0.50-5.12, p=0.430). (Leibovich et al, 2004) In a similar vein, Patard et al noted that 3 year disease-specific survival rates were comparable at 98% and 97% (p=0.8) when partial nephrectomy patients were stratified by tumor size less than and greater than 4cm, respectively.…”
Section: Partial Nephrectomy Is Increasingly Being Utilized In Mediummentioning
confidence: 99%